PENGARUH KOMITMEN ORGANISASI, KOMPETENSI DAN KEMAMPUAN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN ASAHAN - Normansyah, Normansyah (Universitas Labuhanbatu, 2021)
The theory used in this paper is the theory of management of organizations and human resources by focusing more on faktorkomitmen organasasi, competence, work ability and work performance to be the variables in this study. The method used in this research is a survey approach.this type of research is descriptive and quantitative nature of the research is the explanation. Method of data collection is by interview, questionnaire and documentation study. The population is all employees at the Department of Population and Civil registration District of Asahan yaitu31pegawai and set the number of samples of the entire population that there are as many as 31pegawai. Based on the multiple linear equation which is obtained as the following that Å¶ = 2,933+ 0,394 X1 + 0,292 X2 + 0,469 X3 + e. In these equations it can be seen that organizational commitment (X1), competence (X2) and work ability(X3) has a positive regression coefficient that prove its contribution to job performance (Y) of employees in the Department of Population and Civil registration Asahan District in the regression model. Testing simultaneously shows that the value of Fcount (231,921) is large compared with the value of Ftable (2,96), and sig. Î± (0,000 a) is smaller than alpha 5% (0,05). This shows that the variable of organizational commitment, competence and ability to work in serempakberpengaruh on employee job performance in the Department of Population and Civil registration District of Asahan. Partial test results obtained for the organizational commitment (3,262), competence(2,984) and work ability(5,593).Thus the partial dominant influence on employee job performance in the Department of Population and Civil registration District of Asahan is a variable ability to work.